Inhibition of return, gap effect and saccadic reaction time to a visual target - S. Guimarães-Silva; L.G. Gawryszewski; T.S. Portugal; L. Klausner-de-Oliveira (Brazilian Journal of Medical and Biological Research, 2004)
Simple manual reaction time (MRT) to a visual target (S2) is shortened when a non-informative cue (S1) is flashed at the S2 location shortly before the onset of S2 (early facilitation). Afterwards, MRT to S2 appearing at the S1 location is lengthened (inhibition of return - IOR). Similar results have been obtained for saccadic reaction time (SRT). Moreover, when there is a temporal gap between offset of the fixation point (FP) and onset of a target (gap paradigm), SRT is shorter than SRT in an overlap paradigm (FP remains on). In the present study, we determined SRT to S2 (10º) after presenting S1 at the same eccentricity (10º) or at a parafoveal position (2º) in the same or in the opposite hemifield. In addition, we employed both gap and overlap paradigms. Twelve subjects were asked not to respond to S1 (2º or 10º) to the right or to the left of FP, but to respond by making a saccadic movement in response to S2. We obtained the following results: 1) a 40-ms gap effect, 2) an interaction between gap effect and IOR, 3) a 39-ms delay (IOR) when S2 appeared at the cued (S1) position, and 4) a smaller (17 ms) but significant inhibition when S1 occurred at 2º in the ipsilateral hemifield. Thus, a parafoveal (2º) S1 elicits an inhibition of SRT towards ipsilateral peripheral targets. Since an inhibition of the ipsilateral hemifield by a 1º eccentric cue has been reported to occur when manual responses are employed, we suggest that the postulated functional link between covert and overt orienting of attention is also valid for parafoveal cues.